The Effect of Turmeric Simplicia’s (Curcuma longa L.) Washing Treatment on Total Ash, Total Plate Count, Yeast and Mold Count and Curcumin Level - Harnanda Putri, Margaretha; Kawiyanto, Joko; Hartati, Puji; Nurraudah, Siti; Ahmad, Nazir (Universitas Ahmad Dahlan, 2025)
Turmeric (Curcuma longa L.) is one of the traditional plants of Indonesia that has antibacterial activity, helps reduce fever, osteoarthritis, and digestive disorders. The washing process of simplicia is one of the sorting processes in post-harvest handling. This study aims to obtain the best washing method for simplicia with several washing treatments against the total ash content, Total Plate Count (TPC), Yeast and Mold Count (YMC), and curcumin content in turmeric simplicia and turmeric extracts. The study was conducted experimentally with 6 variations of simplicia washing treatments, namely without washing, washing with running water, washing with water at 50°C, washing with 0.2% NaOH, washing with 0.05% HCl, and washing with 2.0% acetic acid. The results showed that washing with 2.0% acetic acid produced the lowest total ash content of the extract at 1.87%. Washing with 50°C water provided the lowest TPC value test data of 6.7 CFU/g, washing with 50ºC water provided the highest curcumin content test data of 9.38%. Based on several parameters of the test results, the washing process chosen was washing the simplicia using 50ºC water which showed high curcumin levels, TPC and YMC values that met the requirements, as well as the ease and safety of the washing method.